Projectile Impact Point Prediction Based on Self-Propelled Artillery Dynamics and Doppler Radar Measurements. (31st December 2013) - Khalil, Mostafa; Rui, Xiaoting; Zha, Qicheng; Yu, Hailong; Hendy, Hossam
Abstract : Any trajectory calculation method has three primary sources of errors, which are model error, parameter error, and initial state error. In this paper, based on initial projectile flight trajectory data measured using Doppler radar system; a new iterative method is developed to estimate the projectile attitude and the corresponding impact point to improve the second shot hit probability. In order to estimate the projectile initial state, the launch dynamics model of practical 155 mm self-propelled artillery is defined, and hence, the vibration characteristics of the self-propelled artillery is obtained using the transfer matrix method of linear multibody system MSTMM. A discrete time transfer matrix DTTM-4DOF is developed using the modified point mass equations of motion to compute the projectile trajectory and set a direct algebraic relation between any two successive radar data. During iterations, adjustments to the repose angle are made until an agreement with acceptable tolerance occurs between the Doppler radar measurements and the estimated values. Simulated Doppler radar measurements are generated using the nonlinear six-degree-of-freedom trajectory model using the resulted initial disturbance. Results demonstrate that the data estimated using the proposed algorithm agrees well with the simulated Doppler radar data obtained numerically using the nonlinear six-degree-of-freedom model.